Do Cashless Transactions and Credit Distribution Affect Inflation in Indonesia? - Firmansyah, Muhammad; Boedirochminarni, Arfida; Riyanto, Wahyu Hidayat; Tsalasa, Arini Roro Anggun (Jurusan Ilmu Ekonomi dan Studi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Lambung, 2024)
The relationship between credit and non-cash transactions includes various mechanisms that affect the money supply, ultimately increasing inflation. One way to control inflation is to maintain the circulation of money. This study provides an understanding of the impact of these transactions on inflation, especially in Indonesia. It aims to test whether cashless transactions, working capital credit, and consumer credit significantly affect Indonesia's inflation rate in both the short and long term. This study was quantitative in nature. It involved statistical analysis techniques through the Error Correction Model (ECM), t-test analysis, and F-test to determine the effect of independent variables on dependent variables both partially and simultaneously. The results revealed that cashless transactions, working capital credit, and consumer credit had a positive and significant effect on the inflation rate in Indonesia in both the short and long term. These results suggest that a more in-depth approach to economic policy is needed, especially focusing on the synergy between fiscal policy, technological developments, and inflation dynamics.